2022
DOI: 10.3390/nano12142480
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal-Based Catalysts with Core-Shell Structure for Oxygen Reduction Reaction: Progress and Prospective

Abstract: With the deterioration of the ecological environment and the depletion of fossil energy, fuel cells, representing a new generation of clean energy, have received widespread attention. This review summarized recent progress in noble metal-based core–shell catalysts for oxygen reduction reactions (ORRs) in proton exchange membrane fuel cells (PEMFCs). The novel testing methods, performance evaluation parameters and research methods of ORR were briefly introduced. The effects of the preparation method, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…This is due to alloying, an enzymatic activity dependent on the compositions as the electronic structure changes. Growing with active nanomaterials or doping with another element is a cost-effective way to tune the activity ( 70 ).…”
Section: Noble Metal Biomimetic Nanozymesmentioning
confidence: 99%
“…This is due to alloying, an enzymatic activity dependent on the compositions as the electronic structure changes. Growing with active nanomaterials or doping with another element is a cost-effective way to tune the activity ( 70 ).…”
Section: Noble Metal Biomimetic Nanozymesmentioning
confidence: 99%
“… 90 Through the combination of these effects and theoretical calculation, core–shell structured noble metal-based nanomaterials with better ORR properties can be reasonably designed and prepared. 91 …”
Section: Noble Metal Oxide-based Electrocatalystmentioning
confidence: 99%
“…Experimental studies have shown that core-shell structural materials have stressstrain relationships between the core and shell layers due to a lattice mismatch. [21][22][23] This stress-strain relationship is one of the reasons for the high electrocatalytic activity of the coreshell structure. Atomic doping produces lattice strain, which affects the electronic structure of the material surface, thereby increasing the electrochemical activity of the material.…”
Section: Introductionmentioning
confidence: 99%